Delay in healthcare seeking for young children with severe pneumonia at Mulago National Referral Hospital, Uganda: A mixed methods cross-sectional study. - Phiona Ekyaruhanga; Rebecca Nantanda; Hellen T Aanyu; John Mukisa; Judith Amutuhaire Ssemasaazi; Mukeere John; Palma Aceng; Joseph Rujumba (PLoS ONE, 2023)
Background Globally, pneumonia is the leading infectious cause of under-five mortality, and this can be reduced by prompt healthcare seeking. Data on factors associated with delays in seeking care for children with pneumonia in Uganda is scarce. Objectives The study aimed to determine the prevalence, factors associated with delay, barriers, and facilitators of prompt healthcare seeking for children under five years of age with severe pneumonia attending Mulago National Referral Hospital (MNRH) Uganda. Methods A mixed methods cross-sectional study was conducted among 384 caregivers of children with severe pneumonia at MNRH. Quantitative data was collected using interviewer-administered structured questionnaires and qualitative data through focus group discussions with caregivers. Descriptive statistics were used to determine the prevalence of delay in care seeking. Logistic regression analysis was used to determine the factors that were independently associated with delay in seeking healthcare. Content thematic analysis was used to analyze for barriers and facilitators of prompt healthcare seeking. Results The prevalence of delay in seeking healthcare was 53.6% (95% CI: 48.6-58.6). Long distance to a hospital (AOR = 1.94, 95% CI 1.22-3.01, p value = 0.003), first seeking care elsewhere (AOR = 3.33, 95% CI 1.85-6.01, p value = 0.001), and monthly income ≤100,000 UGX (28 USD) (AOR = 2.27,95% CI 1.33-3.86, p value = 0.003) were independently associated with delay in seeking healthcare. Limited knowledge of symptoms, delayed referrals, self-medication, and low level of education were barriers to prompt healthcare seeking while recognition of symptoms of severe illness in the child, support from spouses, and availability of money for transport were key facilitators of early healthcare seeking. Conclusion This study showed that more than half of the caregivers delayed seeking healthcare for their children with pneumonia symptoms. Caregivers who first sought care elsewhere, lived more than 5 km from the hospital, and earned less than 28 USD per month were more likely to delay seeking healthcare for their children with severe pneumonia. Limited knowledge of symptoms of pneumonia, self-medication, and delayed referral hindered prompt care-seeking. Key facilitators of prompt care-seeking were accessibility to health workers, support from spouses, and recognition of symptoms of severe illness in children. There is a need for programs that educate caregivers about pneumonia symptoms, in children less than five years.